A cross‐sectional analysis of Wits and Riedel in adults with skeletal III malocclusion: How informative are they?. (6th April 2018) - Oliver, G. R.; Grimes, K.; Pandis, N.; Fleming, P. S.
Structured Abstract: Objectives: To compare the relationship between Riedel and Wits appraisal in skeletal III malocclusions and to assess the effect of variation in the vertical skeletal measurements. Setting and Sample Population: One‐hundred and twenty consecutive subjects with Class III malocclusions attending orthognathic clinics were analysed. Materials and Methods: Lateral cephalograms were hand‐traced under standardized conditions. Cephalometric measurements included Riedel analysis, Wits appraisal, A point/B point to Frankfurt plane (AF‐BF) and vertical measurements. Results: The mean ANB and Wits values were −3.22° and −11.39 mm, respectively. A positive correlation was found between ANB and Wits overall ( r  = −.49; P  < .001). However, there was poor agreement between both Wits ( r  = .087) and Riedel ( r  = .089) with AF‐BF ( P  > .05). A negative correlation existed between Wits and LAFH% ( r  = −.64, P ‐value < .001); however, no relationship was observed between ANB and LAFH% ( P  > .05) based on linear regression analysis. Conclusions: There is a positive relationship between ANB and Wits; however, neither correlated well with a purer antero‐posterior assessment (AF‐BF). Furthermore, variations in the vertical skeletal measurements affect the strength of agreement. Caution is advised in the interpretation of antero‐posterior analysis especially in the presence of vertical discrepancy.